Students’ Awareness in Performing Congregational Prayers to Prevent Radicalism - Muhiddinur Kamal; Nuraisyah Nuraisyah; Muhammad Taufik; Nelmaya Nelmaya; Nofri Andy; Penmardianto Penmardianto (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research aimed to revealed and examined how groups of religious groups, especially student groups who are members of the congregational prayer community, provided students with the correct religious understanding to prevent radicalism on campus. The participants of this study were student religious groups belonging to the congregational prayer movement for students on campus. The number of informants in this study was 48 people with the snowball sampling technique according to research needs and the fulfillment of information. The method used is a qualitative method with interpretive analysis that reveals the meaning and analyzes facts systematically. The findings of this study were that student religious groups who broadcasted and socialized congregational prayers in can provide students with a true religious understanding and could prevent radicalism with a narrow religious understanding.